The Impact of Payment System Digitalization on Customer Satisfaction at PT. Bank Perekonomian Rakyat (BPR) Kawan, Dau District, Malang Regency - Yosefina Jewarus; Anung Prasetyo Nugroho; Fitria Setyaningrum (IRDH International Journal of Social Sciences & Humanities, 2026)
The purpose of this study is to find out how the digitization of the payment system has an impact on customer satisfaction of PT. Kawan People's Economic Bank, Dau District, Malang Regency. This research is a quantitative research that uses a causal associative approach. The population uses all active customers at PT Bank Perekonomian Rakyat (BPR) Kawan, Dau District, Malang Regency which uses digital payment system services totaling 325 people. A total of  77 people were determined through purposive sampling methods.  Instructors use surveys.  Data analysis was carried out using simple linear regression analysis. To test the hypothesis, a (partial) t-test is used. The results of multiple linear regression showed a positive regression coefficient value and a long square value (R2) of 0.567, which showed an influence contribution of 56.7%. In addition, the tcal value is greater than the ttable value (9.917 is greater than 1.992), and its significance value is 0.000, which indicates that the p-value < 0.05. Therefore, it is concluded that the digitization of the payment system has a positive and significant effect on customer satisfaction at PT. Kawan People's Economic Bank, Dau District, Malang Regency. The management of PT. Bank Perekonomi Rakyat Kawan is advised to continue to improve the quality and development of payment system digitalization in a sustainable manner, especially in terms of system reliability, transaction security, and ease of use of services, as well as strengthen digital literacy education programs for customers so that the use of digital services can run optimally and evenly.